DALILA - Design architectures in a Living Lab - Miguel Duarte Mendonça Campos (2019)
This thesis provides an overview of Microgrids and Multi-Microgrids control architectures and validates control functionalities through the combined efforts of numerical simulation and practical tests in a real laboratory by using Power Hardware In the Loop (PHIL) technology. The thesis is divided in five major topics. The first topic is related with Microgrids, Multi-Microgrids and Smartgrids. It starts by describing the context of such concepts and their implications on power systems: the operational challenges they brought along are laid out in order to make sense out of the proposed solutions. Afterwards it details what characterizes these concepts and the essential components behind them. The devices that enable main functionalities such as autonomous operation, active demand response, voltage/var control, blackstart, etc. This involves explaining the models of microgeneration units, storage devices, electric vehicles and system coordinators. Lastly, there is mentioning to some international reference projects. The second topic is related with Living Labs. In order to conduct experiments regarding Microgrids/Smartgrids, it is necessary to identify key laboratory infrastructures and their main experimental objectives. Therefore, a brief outlook of the most notorious international laboratories and their topics of research is presented. The third topic revolves around the simulation mechanics and the software utilized to study power systems behaviour, which in this case was Matlab Simulink. A base case of a Multi-Microgrid system scenario was built based on an existing rural grid and is presented. The MicroSource modelling and the control strategy implemented are described and test results are driven and analysed. The fourth topic details the theory associated with the PHIL converter and describes the series of steps to be followed that allow interaction with Simulink and proper operation. Finally, the last topic describes the experimental tests that were under carried in the laboratory and their respective results. These results will serve to validate the ones obtained in the simulation environment. This serves the purpose of demonstrating microgrid operation and testing.